A feasibility study on elliptical ultrasonic assisted grinding of sapphire substrate. (7th July 2010) - Liang, Zhiqiang; Wang, Xibin; Zhao, Wenxiang; Wu, Yongbo; Sato, Takashi; Lin, Weimin
An elliptical ultrasonic assisted grinding method is proposed for the machining of sapphire substrate in order to improve the machining efficiency and the work-surface quality. An elliptical ultrasonic vibrator is designed and produced by bonding a piezoelectric ceramic device (PZT) on a metal elastic body. The sapphire substrate is fixed onto the top face of the vibrator and ultrasonically vibrates in two dimensional (2D) vibration mode when the PZT is excited by two alternating current voltages with a phase difference. Grinding experiments are carried out with lateral modulation of elliptical vibration vertical to grinding speed direction. Experimental results show that grinding forces decrease significantly by 30% and grinding force ratio is reduced and surface roughness is improved by 15%, moreover surface fractures and cracks decrease obviously by using vibration compared with those of conventional grinding. These demonstrate that two-dimensional ultrasonic grinding is effective for high performance machining of sapphire substrate.